2014
DOI: 10.1249/mss.0b013e3182a10ce6
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acid Amide Hydrolase in Lymphocytes from Sedentary and Active Subjects

Abstract: IL-6 leads to activation of the FAAH promoter, thus enhancing FAAH activity that modulates the eCB tone in physically active people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…This could be because the eCB levels in this study were measured at the basal state, while Heyman et al [61] measured eCB levels after intense exercise. In support to our data, regarding the specific relationships between some NAEs and PA, Gasperi et al [62] found increased activity of FAAH in the lymphocytes of physically active subjects at resting condition. It must be noted that blood eCB levels represent the spillover from many sources and it is not possible to differentiate the tissue of origin.…”
Section: Discussionsupporting
confidence: 92%
“…This could be because the eCB levels in this study were measured at the basal state, while Heyman et al [61] measured eCB levels after intense exercise. In support to our data, regarding the specific relationships between some NAEs and PA, Gasperi et al [62] found increased activity of FAAH in the lymphocytes of physically active subjects at resting condition. It must be noted that blood eCB levels represent the spillover from many sources and it is not possible to differentiate the tissue of origin.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown, in a previous report, that physical activity level (Pittaluga et al 2006) may influence cellular response to oxidative stress. Besides, we also documented that lifestyle (e.g., sedentary vs. active) (Gasperi et al 2014) has an impact on endocannabinoid system, a ubiquitous and complex signaling network involved in various biological processes including those triggered by physical exercise. It is well known that contractile activity increases ROS, which are normally partially neutralized by the cellular antioxidant buffering capacity.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, high circulating AEA concentrations are also associated with high BMI. On the other hand, no differences in basal concentrations of AEA and 2-AG were found between active and sedentary NW men in another study (Gasperi et al, 2014).…”
Section: Circulating Endocannabinoids and Exercisementioning
confidence: 77%